Successful Management of Refractory Heart Failure and Multi-Organ Dysfunction in a Patient with CRT-D and Acute Pulmonary Edema: A Case Report - Marsela Goga; Saimir Kuci; Alfred Ibrahimi; Ermal Likaj; Alvi Cela; Romina Teliti; Ormir Shurdha; Erilda Selimi; Jacob Zeitani (Albanian Journal of Trauma and Emergency Surgery)
Introduction: Heart failure with reduced ejection fraction (HFrEF) is a progressive condition often complicated by acute decompensations that require advanced medical interventions. Cardiac resynchronization therapy with a defibrillator (CRT-D) has significantly improved outcomes in patients with severe heart failure. However, challenges persist when faced with acute events such as pulmonary edema, pneumonia, and multi-organ dysfunction syndrome. Multidisciplinary, intensive care unit (ICU)-based management is critical for these complex cases.